FORMATION OF COGNITIVE-VISUAL SKILLS IN THE ACTIVITY OF TEACHERS - Jakhongir Botirov (Journal of Higher Education and Academic Advancement, 2024)
This article provides a reference to the formation of cognitive and visual skills in the activities of teachers, the importance of cognitive and visual skills and their role in human life.